Vie privée, morale publique : le fascisme et le « problème » homosexuel - Lorenzo Benadusi (Genre, Sexualité et Société)
This article analyses the Fascist attitude towards homosexuals, the strategies and motivations for repressive actions taken against them, and the masculine canon and lifestyle that the Fascist regime tried to disseminate. The emphasis placed on sexual morality and virility, as well as accusations of “pederasty”, allows us to understand the political use of the question of homosexuality in personal rivalries to gain positions of power and discredit opponents or create distance from inconvenient figures. At the same time, disapproval of homosexuality was not always applied in practice. Individuals who led a double life, yet formally adhered to the standards of respectability, were able to elude the encroachment of politics and repressive actions in their lives. Homosexuality, in fact, was tolerated as long as it remained within the private sphere. So the analysis of this thorny relationship between public and private reveals the impact of the Fascist totalitarian experiment on customs and daily life, as well as the difficulties encountered by the regime in implementing its anthropological revolution of the Italian people.